Pengaruh Audit Tenure, Ukuran KAP, dan Struktur Kepemilikan Perusahaan terhadap Kualitas Audit dengan Spesialisasi Auditor sebagai Variabel Moderating - Ananda, Muhammad Rizky; Adam Zakaria; Tri Hesti Utaminingtyas (Jurnal Akuntansi, Perpajakan dan Auditing, 2023)
The Effect of Audit Tenure, KAP Size, and Company Ownership Structure on Audit Quality with Auditor Specialization as a Moderating Variable. Thesis, Jakarta: Faculty of Economics, State University of Jakarta, 2023. This study aims to This study aims to determine the effect of audit tenure, hood size, and company ownership structure on audit quality with auditor specialization as a moderating variable. In this study, the population used was companies in the transportation & logistics sector listed on the IDX during the 2018-2020 period. The results of this study indicate that the significant value of the audit tenure variable is 0.165 and with these results showing a value greater than the significance value used in this study, namely 0.05, so that based on the results of these findings it can be concluded that audit tenure has no effect on audit quality.